PROBLEMS OF PREPARATION FOR ENTREPRENEURSHIP IN THE SYSTEM OF VOCATIONAL EDUCATION AND TRAINING IN THE EUROPEAN EDUCATIONAL AND SCIENTIFIC SPACE (Innovative professional education, 2023)
The structure and nature of vocational education and training are undergoing rapid changes in the context of globalization and European integration. EU member states have outlined the main goals of this educational subsystem in the Concept and Strategy for Lifelong Learning, which is based on fundamental principles: promoting the development of new fundamental skills, increasing investment in human resource development, encouraging innovation in teaching and learning, assessing learning outcomes, including non-formal and informal learning, improving career guidance and counseling services, and expanding access to education for those who wish to learn. The study of modern models of vocational education and training in the European Union can be seen as a means of gaining innovative experience that can enhance the reputation and status of national vocational education in the context of cooperation between Ukraine and the EU. It can also contribute to the reform and integration of vocational education into the European and global educational and scientific space.
Keywords: professional education, problems of preparation for entrepreneurship, development of entrepreneurial competence, qualities of a successful entrepreneur